A Review of Complicated Cataract in Retinitis Pigmentosa: Pathogenesis and Cataract Surgery - Yingying Hong; Hongzhe Li; Yang Sun; Yinghong Ji (Journal of Ophthalmology)
Retinitis pigmentosa (RP) is a set of inherited retinal degenerative diseases that affect photoreceptor and retinal pigment epithelial cells (RPEs), possibly associated with some ocular complications, including cataract. The complicated cataract formation is most likely the result of RP-related inflammation response, and the most common morphology category is posterior subcapsular cataract (PSC). Despite the absence of curative pharmacologic treatment, phacoemulsification with intraocular lens implantation to deal with opacification in the lens is preferred due to the considerable visual outcomes. However, the incidence of intraocular and postoperative complications is higher in RP patients than those without, including intraoperative phototoxic retinal damage, posterior capsular opacification (PCO), capsular contraction syndrome (CCS), pseudophakic cystoid macular edema (PCME), increased postoperative intraocular pressure (IOP), and intraocular lens (IOL) dislocation. Hence, it needs much attention to surgery progress and close follow-up. In this review, we discuss the current understanding of RP patients with complicated cataracts from morphology to potential pathogenesis to cataract surgical procedure and provide a concise description and the recommended management of related surgery complications to broaden the knowledge and lower the latent risks to yield better clinical outcomes.